Veterinarian and Para-Veterinarian Perceptions on Canine Hookworms and Riley County’s Community Health Improvement Plan Assessment - Ochoa, Sara (My University, 2022)
Canine hookworms (Ancylostoma caninum) are zoonotic intestinal parasites that cause anemia and weight loss in dogs and Cutaneous Larva Migrans in humans, demanding a One Health perspective. This perspective allows veterinarians, health care providers, and others to collaborate to achieve optimal health outcomes for their patients. Overuse of anthelmintics (dewormers) over time has caused the emergence of resistance in several populations of canine hookworms. Anthelmintic resistant hookworms have now spread to many canine breeds. Given the major role of veterinarians, the goal of this cross-sectional study was to obtain a better understanding of current practices and veterinarians’ perceptions about diagnosing, treating, and controlling canine hookworms. The survey was taken by 180 veterinarians in 42 states between February and March 2022. We found that 67% of surveyed veterinarians answered they were aware of hookworm prevalence in dogs in their area within the last year. Many respondents (46%) answered that there was no breed predilection but hounds (42%), mixed breed dogs (26%), and pit bulls (17%), were perceived to have a higher predilection. Roughly 36% responded it is very common for dogs with hookworms to be asymptomatic. Most veterinarians (48%) mentioned that their patients are on annual broad-spectrum preventatives that include hookworms. About 43% of veterinarians stated that they have dealt with a hookworm positive dog suspected of drug resistance or reinfection and had to change the course of treatment. Client education on zoonotic infection was always performed by 26% of veterinarians. Control measures advocated include removing feces from yards or parks, prevention of scavenging, having pets on monthly preventatives, and enforcing leash laws. The results from this survey will help veterinarians better consult with clients in the future as well as create a more effective course of treatment, in light of emerging drug resistance in hookworms.
Keywords: Hookworms; Canine; Veterinarians; Para-Veterinarians; Survey; Parasite